Determinan Internal, Eksternal Dan Refleksivitas Kesejahteraan Dusun Rabak - Aziz, Roikhan; Utami, Puji; Ariani, Gita Novi; Bimo, Ario; Limbong, Ilham Syahbana (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2018)
The objective of this study were the writers was describing the result of KKN program that already held from July 25th, 2017 until August 25th, 2017 in Rabak, Rumpin. However, the writers would like to explain the result of analysis using S.W.O.T analysis into the empowerment programs and the result will be described as descriptive qualitative and quantitative method. The results of this study indicate that the community dvelopment in village of Rabak has a very rich nature, especially its natural resources to farm, but the wealth that exist in the natural village of Rabak is not in line with its destructive nature management that has existed for a long time. With the results of this study, researchers a little help Rabak Village with creative economic activity program from Rakan Indonesia. There the mothers and parents follow the activity, to increase their insight in managing opportunities and teach how to make accessories that have high selling power.